Evaluation of the cumulative effect of photodynamic therapy and local fluoride on the microhardness and topography of demineralized enamel and cementum surfaces - Sedighe Sadat Hashemikamangar; Mahtab Vahedi; Mohammadreza Khadivi Moghadam; Behnaz Behniafar; Nasim Chiniforush (Heliyon, 2024)
Background: The present study aimed to determine the cumulative effect of two photodynamic therapy methods with methylene blue and indocyanine green and two topical fluoride therapy methods with fluoride varnish and silver diamine fluoride alone and in combination on the microhardness and topography of demineralized enamel and cementum surfaces. Materials and methods: Seventy-two sound human teeth were selected, and their buccal and lingual surfaces were assigned to two main groups of enamel and cementum using simple randomization. The initial surface hardness (SH) of the enamel and cementum in each sample was determined using a micro-Vickers hardness tester using a 200-g force in 10 s. Then artificial caries was induced by immersion in a demineralizing/remineralizing solution (i.e., each tooth provided two samples, one on the buccal aspect and the other on the lingual aspect). Each enamel/cementum main group was divided into two subgroups using simple randomization based on the local fluoride type (fluoride varnish and silver diamine fluoride) and the type of the photosensitizer agent (methylene blue and indocyanine green). Finally, 16 groups were achieved (n = 9). The final surface hardness of the enamel and cementum samples was determined as described above. Finally, the sample surfaces were prepared for the surface topography evaluation under a scanning electron microscope. The baseline microhardness was compared between the 16 study groups in the first step using one-way ANOVA. Then, three-way ANOVA was used to evaluate the effect of fluoride, laser, and surface (enamel and cementum) on microhardness. Results: All the groups exhibited decreased microhardness due to the induction of artificial caries. In both main groups of enamel and cementum, the lowest decrease in microhardness was recorded with combined photodynamic therapy and methylene blue photosensitizer material and fluoride varnish (15.1 % for cementum and 16.7 % for enamel), and the highest decrease in microhardness was recorded in the methylene blue group (35.7 % for cementum and 34.9 % for enamel). Conclusion: The combination of photodynamic therapy with the photosensitizer substance methylene blue or indocyanine green together with fluoride varnish or silver diamine fluoride is effective on the remineralization of demineralized enamel and cementum. Although there is no difference between the combination of photodynamic therapy with fluoride varnish compared to fluoride varnish alone, both of these treatments are more effective than using photodynamic therapy alone.